69.7k views
2 votes
Solve the equation 6.8x + 9.3 = -9.4 + 3.4 (2-5x)

User ElDog
by
5.6k points

2 Answers

4 votes

Answer:

x = -0.5

Explanation:


6.8x + 9.3 = -9.4 + 3.4 (2-5x)\qquad\text{multiply both sides by 10}\\\\68x+93=-94+34(2-5x)\qquad\text{use distributive property}\\\\68x+93=-94+(34)(2)+(34)(-5x)\\\\68x+93=-94+68-170x\\\\68x+93=-26-170x\qquad\text{subtract 93 from both sides}\\\\68x=-119-170x\qquad\text{add 170x to both sides}\\\\238x=-119\qquad\text{divide both sides by 238}\\\\x=-(119)/(238)\\\\\boxed{x=-(1)/(2)}

User Chandresh
by
5.6k points
2 votes

Answer:

x = -.5

Explanation:

6.8x + 9.3 = -9.4 + 3.4 (2-5x)

Distribute the 3.4

6.8x + 9.3 = -9.4 + 6.8 - 17x

Combine like terms

6.8x + 9.3 = -2.6 -17x

Add 17x to each side

6.8x+17x + 9.3 = -2.6-17x+17x

23.8x +9.3 = -2.6

Subtract 9.3 from each side

23.8x +9.3-9.3 = -2.6-9.3

23.8x = -11.9

Divide by 23.8

23.8x/23.8 = -11.9/23.8

x = -.5

User Andrew Sawa
by
5.2k points